SOLPS-ITER modification for impurity transport modelling in the tokamak pedestal region - V. Korzueva; E. Kaveeva; V. Rozhansky; X. Bonnin (Nuclear Materials and Energy, 2025)
Kinetic corrections to SOLPS-ITER fluid equations are made to extend their applicability for description of the neoclassical part of impurity transport to collisionless regimes of the main ions. Analysis is performed of impurity transport for the H-mode transport edge barrier and pedestal for several tokamaks: ASDEX-Upgrade, JET and ITER based on SOLPS-ITER modelling. Poloidal distribution of impurities and their radial fluxes are studied in detail. Significant difference of impurity drift flows with respect to neoclassical theory predictions is obtained for JET and ASDEX-Upgrade, while for ITER the drift flows reproduce neoclassical transport.